Application of fuzzy logic approach to structure based compariso of in-parallel planar manipulators - Rao, AB Srinivasa (Kathmandu University Journal of Science Engineering and Technology, 2010)
Planar In-parallel Manipulations, which are nothing but multi degree-of-freedom closed kinematic chains can be modelled as fuzzy systems, so that the fuzzy logic can be applied. It is shown that the fuzzy entropy can be utilized to compare numerous distinct chains, with the same number of links and degrees of freedom from the view point of parallelism so that the designer can have an idea, at the conceptual stage of design regarding suitability of chains, from the view point of rigidity, work space and accumulation of joint errors. Spatial chains are also dealt with. Aspect of work space is verified experimentally.